Characterizing the Functional and Cosmetic Outcomes of Pedicled Neck Flaps in Patients Who Underwent Partial Tongue Resection: A Systematic Review - Atmodiwirjo, Parintosa; Ralena, Nadhira Anindita; Ramadan, Mohamad Rachadian; Triatmoko, Sara Ester (Jurnal Plastik Rekonstruksi, 2021)
Introduction: Pedicled flaps from infrahyoid, pectoralis major, and trapezius were commonly used for partial tongue reconstruction. Not until a free radial forearm flap was introduced. The flap is recommended for patients with tongue defects ? 50% because of its thinness, pliability, and long pedicle. This systematic review explores the functional and cosmetic outcomes of pedicled flaps from the neck region for patients who underwent partial tongue resection or hemiglossectomy. Method: A systematic literature searching was performed on PubMed, Medline, Scopus, Embase, and Cochrane. Keywords included were pedicled flap, neck flap, partial tongue resection, hemiglossectomy, and partial neck surgery. Inclusion and exclusion criteria were applied to the search results. Relevant studies were assessed for their methodological quality using appropriate instruments. Results: Four hundred and twenty-four articles were obtained from the initial literature search. The authors finally gathered 11 full-text articles comparing the pedicled neck flaps with free flaps for partial tongue resection reconstructions. Pedicled neck flaps, such as submental, infrahyoid, sternocleidomastoid, and supraclavicular artery island flap, are clinically relevant for hemiglossectomy reconstruction with comparable functional and aesthetic outcomes. Conclusion: Regional flaps would be a preferred technique in more difficult patients such as those with advanced age, poor nutrition, or multiple medical issues as they are not always acceptable surgical candidates for potentially prolonged microsurgery.